Genetically predicted associations between circulating cytokines and autoimmune diseases: a bidirectional two-sample Mendelian randomization - Jie, Jie; Gong, Yonglu; Luo, Songquan; Yang, Xing; Guo, Kaiyun (Frontiers in Immunology, 2024)
Objectives Previous studies have indicated a correlation between cytokines and autoimmune diseases. yet the causality remains uncertain. Through Mendelian Randomization (MR) analysis, we aimed to investigate the causal relationships between genetically predicted levels of 91 cytokines and three autoimmune diseases: Multiple Sclerosis (MS), Systemic Lupus Erythematosus (SLE), and Hashimoto’s Thyroiditis (HT). Methods A bidirectional two-sample MR approach was utilized to assess the causal relationships between cytokines and MS, SLE, and HT. The datasets included 47,429 MS cases and 68,374 controls, 5,201 SLE cases and 9,066 controls, and 16,191 HT cases with 210,612 controls. Data on 91 cytokines comprised 14,824 participants. Causal analyses primarily employed inverse variance weighted, weighted median, and MR-Egger methods, with sensitivity analyses including heterogeneity and pleiotropy assessment. Results Genetically predicted levels of IL-18 (OR = 0.706; 95% C.I. 0.538–0.925), ADA (OR = 0.808; 95% C.I. 0.673–0.970), and SCF (OR = 0.898; 95% C.I. 0.816–0.987) were associated with a decreased risk of MS. IL-4 (OR = 1.384; 95% C.I. 1.081–1.771), IL-7 (OR = 1.401; 95% C.I. 1.010–1.943), IL-10RA (OR = 1.266; 95% C.I. 1.004–1.596), CXCL5 (OR = 1.170; 95% C.I. 1.021–1.341), NTN (OR = 1.225; 95% C.I. 1.004–1.496), FGF23 (OR = 0.644; 95% C.I. 0.460–0.902), and MCP4 (OR = 0.665; 95% C.I. 0.476–0.929) were associated with SLE risk. CDCP1 (OR = 1.127; 95% C.I. 1.008–1.261), IL-33 (OR = 0.852; 95% C.I. 0.727–0.999), and TRAIL (OR = 0.884; 95% C.I. 0.799–0.979) were associated with HT risk. Bidirectional MR results suggest the involvement of CCL19, IL-13, SLAM, ARTN, Eotaxin, IL-22RA1, ADA, and MMP10 in the downstream development of these diseases. Conclusions Our findings support causal relationships between certain cytokines and the risks of MS, SLE, and HT, identifying potential biomarkers for diagnosis and prevention. Additionally, several cytokines previously unexplored in these autoimmune disease contexts were discovered, laying new groundwork for the study of disease mechanisms and therapeutic potentials.